A Certified Copy: Translating Images in the Eighteenth-Century French Print Market - Abramovitch, Tamara (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
In an era before the invention of photography, fine art prints based on famous paintings dominated the eighteenth-century art market, inviting a common comparison between engravers and translators. At a time when writers and scholars placed much value on the closeness of translations to their original texts, such comparisons reflected a subordination of the skills of technical engravers to the assumed genius of painters. However, careful examination of the copy-prints reveals that loyalty to originals was not the primary interest of these visual translators. Instead, these translators saw themselves as active mediators. This essay reconsiders acts of eighteenth-century visual translation to reframe the practice of engraving during the period and to establish a new understanding of the movement from one visual artistic language to another. The case study of Nicolas de Launay, one the most successful engravers in eighteenth-century France, is selected for scrutiny and contextualized within historical debates around translation. The final aim is to illuminate important tensions between the disciplines of painting and engraving, as well as the complex process by which engravers strove to remain simultaneously loyal to the painters, to their audience, and to their own artistic identity.